2022
DOI: 10.3390/ijms23041964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin in Experimental Pulmonary Tuberculosis: Antimycobacterial Activity in the Lungs and Anti-Inflammatory Effect in the Brain

Abstract: Tuberculosis (TB) is one of the ten leading causes of death worldwide. Patients with TB have been observed to suffer from depression and anxiety linked to social variables. Previous experiments found that the substantial pulmonary inflammation associated with TB causes neuroinflammation, neuronal death, and behavioral impairments in the absence of brain infection. Curcumin (CUR) is a natural product with antioxidant, anti-inflammatory and antibacterial activities. In this work, we evaluated the CUR effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…verified that apoptosis plays an important role in the pathogenesis of TB ( 48 ). It has been reported that in patients with no brain infection, the lungs become infected with Mtb and cause an inflammatory response, which can trigger inflammation in the brain and interfere with neurotrophic factors ( 49 ). Interestingly, Cluster 2 was characterized by an active nervous system, suggesting that the nervous system of these patients may be affected by Mtb.…”
Section: Discussionmentioning
confidence: 99%
“…verified that apoptosis plays an important role in the pathogenesis of TB ( 48 ). It has been reported that in patients with no brain infection, the lungs become infected with Mtb and cause an inflammatory response, which can trigger inflammation in the brain and interfere with neurotrophic factors ( 49 ). Interestingly, Cluster 2 was characterized by an active nervous system, suggesting that the nervous system of these patients may be affected by Mtb.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin significantly reduces neuroinflammation and improves behavioral status by slightly increasing the levels of nuclear factor erythroid 2-related to factor 2 brain-derived neurotrophic factor. 50 Shadnoush et al 30 reported that curcuminoid supplementation has a beneficial effect on serum concentrations of adipokines, but this beneficial effect has not yet been studied in the treatment of critical TBI cases. Placebo-controlled 500 mg/day curcuminoids were administered to 62 critical cases with TBI aged 18 to 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin significantly reduces neuroinflammation and improves behavioral status by slightly increasing the levels of nuclear factor erythroid 2-related to factor 2 brain-derived neurotrophic factor. 50…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from several studies has shown that curcumin has an anticancer, anti‐inflammatory, antioxidant, and lipid‐lowering effect, in addition to thermogenic capacity 58–61 …”
Section: Bioactive Dietary Components and Their Anti‐obesity Effectsmentioning
confidence: 99%
“…57 Evidence from several studies has shown that curcumin has an anticancer, anti-inflammatory, antioxidant, and lipid-lowering effect, in addition to thermogenic capacity. [58][59][60][61] In order to prove its anti-inflammatory effects, the study by Maithilikarpagaselvi et al 62 shows that animals fed with HFD (30%) and supplemented with curcumin (200 mg/kg BW, for 10 weeks) showed a reduction in tumor necrosis factor alpha (TNF-α) levels.…”
Section: Curcuminmentioning
confidence: 99%